Improvement of Black-Odor Water by Pichia Strain GW1 under Optimized NH3-N Degradation Conditions. (18th February 2020) - Xie, Haiwei; Wang, Mingyang; Zeng, Huayang; Yu, Mingrong; Wu, Zijian; Chen, Shuhong; Zhao, Shaotian; Zheng, Jie; Deng, Dun
Abstract : In this study, a yeast strain with an outstanding NH3 -N degradation ability was isolated from the sediment of a black-odor water channel in Guangdong Province, China. Based on phenotypic and phylogenetic analysis, this strain was identified as Pichia kudriavzevii GW1. The optimum conditions for NH3 -N degradation by the GW1 strain were as follows: 0.3% inoculum concentration, 1.5 L/min aeration, pH 7, and a temperature of 35°C. Under optimized conditions, the GW1 strain degraded 95.5% of the NH3 -N. The strain was then added to simulated black-odor water under optimal degradation conditions to investigate changes to the bacterial community over time. 16S rRNA sequencing of samples collected on days 0, 7, 14, and 21 showed that, in the presence of the GW1 strain, the relative abundances of the phyla Proteobacteria, Bacteroidetes, Chloroflexi, and Firmicutes increased in the black-odor water. In addition, the relative abundance of Propionivibrio, a known NH3 -N degrading genus, increased. This study will facilitate the use of microbiological methods to repair black-odor water.